Effect of gentamicin and levels of ambient sound on hearing screening outcomes in the neonatal intensive care unit: A pilot study. (June 2017) - Garinis, Angela C.; Liao, Selena; Cross, Campbell P.; Galati, Johnathan; Middaugh, Jessica L.; Mace, Jess C.; Wood, Anna-Marie; McEvoy, Lindsey; Moneta, Lauren; Lubianski, Troy; Coopersmith, Noe; Vigo, Nicholas; et al.
Abstract: Objective: Hearing loss rates in infants admitted to neonatal intensive care units (NICU) run at 2–15%, compared to 0.3% in full-term births. The etiology of this difference remains poorly understood. We examined whether the level of ambient sound and/or cumulative gentamicin (an aminoglycoside) exposure affect NICU hearing screening results, as either exposure can cause acquired, permanent hearing loss. We hypothesized that higher levels of ambient sound in the NICU, and/or gentamicin dosing, increase the risk of referral on the distortion product otoacoustic emission (DPOAE) assessments and/or automated auditory brainstem response (AABR) screens. Methods: This was a prospective pilot outcomes study of 82 infants (<37 weeks gestational age) admitted to the NICU at Oregon Health & Science University. An ER-200D sound pressure level dosimeter was used to collect daily sound exposure in the NICU for each neonate. Gentamicin dosing was also calculated for each infant, including the total daily dose based on body mass (mg/kg/day), as well as the total number of treatment days. DPOAE and AABR assessments were conducted prior to discharge to evaluate hearing status. Exclusion criteria included congenital infections associated with hearing loss, and congenital craniofacial or otologic abnormalities. Results: The mean level of ambient sound was 62.9 dBA (range 51.8–70.6 dBA), greatly exceeding American Academy of Pediatrics (AAP) recommendation of <45.0 dBA. More than 80% of subjects received gentamicin treatment. The referral rate for (i) AABRs, (frequency range: ∼1000–4000 Hz), was 5%; (ii) DPOAEs with a broad F2 frequency range (2063–10031 Hz) was 39%; (iii) DPOAEs with a low-frequency F2 range (<4172 Hz) was 29%, and (iv) DPOAEs with a high-frequency F2 range (>4172 Hz) was 44%. DPOAE referrals were significantly greater for infants receiving >2 days of gentamicin dosing compared to fewer doses (p = 0.004). The effect of sound exposure and gentamicin treatment on hearing could not be determined due to the low number of NICU infants without gentamicin exposure (for control comparisons). Conclusion: All infants were exposed to higher levels of ambient sound that substantially exceed AAP guidelines. More referrals were generated by DPOAE assessments than with AABR screens, with significantly more DPOAE referrals with a high-frequency F2 range, consistent with sound- and/or gentamicin-induced cochlear dysfunction. Adding higher frequency DPOAE assessments to existing NICU hearing screening protocols could better identify infants at-risk for ototoxicity.